A study on the relationship between leadership behaviour and job satisfaction among academic staff in private Universities in Malaysia / Norela Elias - Elias, Norela (2012)
This study was conducted to investigate the relationship between perceived leadership behavior and job satisfaction among academic staffs of private higher educational institutions in Malaysia. Specifically, the study attempted to 1) investigate the level of job satisfaction and perceived leadership styles of academic staffs of private higher education institutions of Malaysia; 2) identify the relationship of perceived leadership behavior and job satisfaction of academics staffs of private higher education institutions of Malaysia and 3) identify the contributor of each significant of leadership behavior on the variance of job satisfaction.The questionnaire was distributed to a total of 150 randomly selected respondents and the responses rate was 73% or 40 questionnaires were returned and only 110 questionnaires were duly completed and used in analysis. Data were collected using the survey method and were descriptive statistically analysed.From the study, the findings revealed that the level of job satisfaction as perceived by the respondents was at moderate level and perceived transformational and transactional styles were both at moderate but slightly higher for transactional. For the relationship between job satisfaction and the independent variables, the findings suggested that there was a positive and moderate relationship between job satisfaction and transformational leadership. In terms of determining the contributor of each significant of leadership styles on the variance of job satisfaction, it revealed that 8.2% of the variance in job satisfaction scores can be predicted from the variables of transformational leadership.From the findings of the study, it could be summarized that transformational leadership plays a significant role in satisfaction of workers as a whole. In addition, it is also indicated from the study that communication plays a role towards providing job satisfaction among the academic staff in the private educational institution in Malaysia.